2008
DOI: 10.1080/00498250802126920
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II enzyme induction by α-lipoic acid through phosphatidylinositol 3-kinase-dependent C/EBPs activation

Abstract: 1. -Lipoic acid (-LA) activates antioxidant pathways and exerts insulin-like actions via phosphatidylinositol 3-kinase (PI3K), and previous studies from the authors' laboratory support the essential role of PI3K-dependent CCAAT/enhancer binding protein (C/EBP) activation in antioxidant defence responses. 2. The study investigated whether -LA treatment promoted phase II antioxidant gene induction through C/EBP activation and, if so, whether combined treatment of -LA and insulin synergistically increased target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Several in vivo studies have further provided evidence that LA supplementation decreases oxidative stress and restores reduced levels of other antioxidants under various physiologic and pathophysiologic conditions in brain and heart tissues and in RBC (51,52). In addition to acting as a coenzyme and antioxidant, recent work indicates that LA may also act as an inducer of several phase II detoxification enzymes, including GSTA and NQO1 through a CCAAT/enhancer binding protein and Nrf2-dependent pathway (8). In this study, we further showed that LA and DHLA activate AP-1 and Nrf2 translocation into the nucleus, where they bind to GPEI and upregulate GSTP transcription.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several in vivo studies have further provided evidence that LA supplementation decreases oxidative stress and restores reduced levels of other antioxidants under various physiologic and pathophysiologic conditions in brain and heart tissues and in RBC (51,52). In addition to acting as a coenzyme and antioxidant, recent work indicates that LA may also act as an inducer of several phase II detoxification enzymes, including GSTA and NQO1 through a CCAAT/enhancer binding protein and Nrf2-dependent pathway (8). In this study, we further showed that LA and DHLA activate AP-1 and Nrf2 translocation into the nucleus, where they bind to GPEI and upregulate GSTP transcription.…”
Section: Discussionmentioning
confidence: 96%
“…The accumulated evidence supports that garlic alliin-derived allyl sulfides and cruciferous isothiocyanates protect animals against a variety of chemical carcinogens (1,6). This chemoprevention can be partly explained by the potency of these phytochemicals in modulating the activity and gene expression of phase II detoxification enzymes (7)(8)(9).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have indicated that α-lipoic acid increases the mRNA expression or the activity or protein levels of enzymes involved in drug metabolism, including NAD(P)H:quinone oxidoreductase ( 16 18 ) , Gst-α2 and microsomal epoxide hydrolase ( 18 ) , in various types of cultured cells. However, an animal study examining the physiological activity of α-lipoic acid affecting drug-metabolising enzymes has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports showing significant levels of cytoplasmic C/EBPβ in hepatocyte cell lines (Ki and Kim 2008;Lee et al 2007;Yin et al 1996), in a colorectal cancer cell line (Chinery et al 1997) and in thyroid papillary carcinoma cells (Akagi et al 2008;Pomerance et al 2005). Phosphorylation of Ser239 in mouse (Ser288 human), which is part of the NLS, regulates C/EBPβ nuclear transport.…”
Section: C/ebpβmentioning
confidence: 96%